Functional acuity contrast sensitivity assessment in young and middle age healthy persons at the day time with and without glare - Sidorova, Jelena; Čiumbaraitė, Rasa; Čebatorienė, Džastina; Banevičius, Mantas; Liutkevičienė, Rasa (Acta medica Lituanica, 2014)
Background. As people age, their vision becomes less clear; they can clearly see big objects but experience problems discerning minor things and minor details. The functional acuity contrast test is a very sensitive method used for visual system evaluation which may help to detect the beginning of the disease in case the visual acuity is still normal. Purpose. To determine functional acuity contrast sensitivity in young and in middle age healthy persons at the day time with and without glare. Materials and methods. We examined 40–49 yrs (Group 1), and 50– 59 yrs (Group 2) healthy persons. The typical Snellen chart (the direction of the gap in Landolt C) was used for the non-corrected and the bestcorrected visual acuity testing. Functional acuity contrast sensitivity was measured employing a Ginsburg Box, VSCR- CST-6500, at the day time with and without glare. Results. Functional acuity contrast sensitivity remained very similar in the age groups of 40–49 years and 50–59 years. However, statistically, it significantly decreased at day time without glare (18 cycle / degree) spatial frequencies (p = 0.05). Results in Group 1 as compared to Group 2 decreased from 3.09% to 51.7% at the day time without glare and from 2.16% to 11.61% at the day time with glare. Conclusion. The facts are that contrast sensitivity remained very similar in the age groups of 40–49 years and 50–59 years at the day time with and without glare.